2017
DOI: 10.1080/1331677x.2017.1305804
|View full text |Cite
|
Sign up to set email alerts
|

Firm size and job creation: evidence from Turkey

Abstract: This study examines the relationship between firm size and job creation by using an extensive data set covering all non-farm Turkish businesses with 20 or more employees from 2003 to 2010. We find that small firms (firms with employees between 20 and 100 employees) have higher mean job flow rates (job creation, job destruction and net job creation rates) than large firms. Firm size and job flow rates are inversely related, and this relationship is especially prominent for firms with 50 employees or more. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Recently, Neumark et al (2011) provide evidence of the significant contribution of small firms towards job creation in the United States of America. Some other studies too have analyzed the role of small firms and find similar results (see de Wit & de Kok, 2014;Dogan et al, 2017;Hijzen et al, 2010;Huber et al, 2017;Ma et al, 2015;Picot & Dupuy, 1998). However, some studies present findings that contradict the popular view that small firms are the main job creators (Cho et al, 2017;Davis et al, 1996;Kerr et al, 2014) while others have argued that it is not firm size per se that drives job creation but rather the start-up businesses (Haltiwanger et al, 2008(Haltiwanger et al, , 2013Klapper & Richmond, 2011;Lawless, 2014).…”
Section: Introductionsupporting
confidence: 54%
“…Recently, Neumark et al (2011) provide evidence of the significant contribution of small firms towards job creation in the United States of America. Some other studies too have analyzed the role of small firms and find similar results (see de Wit & de Kok, 2014;Dogan et al, 2017;Hijzen et al, 2010;Huber et al, 2017;Ma et al, 2015;Picot & Dupuy, 1998). However, some studies present findings that contradict the popular view that small firms are the main job creators (Cho et al, 2017;Davis et al, 1996;Kerr et al, 2014) while others have argued that it is not firm size per se that drives job creation but rather the start-up businesses (Haltiwanger et al, 2008(Haltiwanger et al, , 2013Klapper & Richmond, 2011;Lawless, 2014).…”
Section: Introductionsupporting
confidence: 54%
“…His findings showed that 81.5 percent of all net new jobs in the United States during 1969-1976 were created by firms with 100 or fewer employees. Similarly, [23] conducted a study in Turkey among non-farm business with 20 -100 employees and concluded that, small firms (firms with employees between 20 and 100 employees) had higher mean job creation rates than larger firms.…”
Section: Empirical Evidencementioning
confidence: 99%
“…The results concerning the impact of size and age on employment rate support those of a number of previous studies (Hall, 1987; Broersma and Gautier, 1997; Oliveira and Fortunato, 2006; Criscuolo et al ., 2014; Yazdanfar and Öhman, 2015), although they stand in contrast to the results of Aga et al . (2015), Pyo et al (2016) and Dogan et al (2017) regarding the size variable, and the results of Voulgaris et al . (2005) and Aga et al .…”
Section: Discussionmentioning
confidence: 86%